2011
DOI: 10.1007/s00296-011-1977-9
|View full text |Cite
|
Sign up to set email alerts
|

Bilirubin levels in patients with systemic lupus erythematosus: increased or decreased?

Abstract: The aim of this study was to investigate the serum bilirubin levels in SLE patients and their associations with clinical and laboratory characteristics of SLE. There were 198 SLE patients in this study, of whom 7 cases with tobacco smoking or alcohol intake were excluded. Some clinical and laboratory characteristics of the patients were obtained by medical record review. In addition, 154 age- and sex- matched healthy volunteers with no histories of SLE, liver diseases, and other autoimmune or inflammatory dise… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
21
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(22 citation statements)
references
References 43 publications
1
21
0
Order By: Relevance
“…[21][22][23][24][25] A number of studies found that bilirubin is a protective factor and decreased in several inflammatory or autoimmune diseases such as atherosclerosis, SLE, RA, PM, and diabetic nephropathy. [14][15][16][17][18][19]26,27 pSS is also a systemic autoimmune disease. It has been suggested that various immune effectors (such as Th1, Th17, T follicular helper, and B cells) may be involved in the pathogenesis of different phases in pSS.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[21][22][23][24][25] A number of studies found that bilirubin is a protective factor and decreased in several inflammatory or autoimmune diseases such as atherosclerosis, SLE, RA, PM, and diabetic nephropathy. [14][15][16][17][18][19]26,27 pSS is also a systemic autoimmune disease. It has been suggested that various immune effectors (such as Th1, Th17, T follicular helper, and B cells) may be involved in the pathogenesis of different phases in pSS.…”
Section: Discussionmentioning
confidence: 99%
“…12,13 Recently, decreased levels of serum bilirubin have been linked to some connective tissue diseases, including systemic lupus erythematosus (SLE), rheumatoid arthritis (RA), polymyositis (PM), the pathogenesis of which involves oxidative stress and inflammatory injury. [14][15][16][17][18][19] However, to our knowledge, there has been no study investigating whether serum bilirubin is decreased in pSS patients. Therefore, in this study, we aimed to determine the serum bilirubin levels in pSS patients and to explore clinical significance of bilirubin in pSS.…”
mentioning
confidence: 99%
“…Bilirubin is a powerful antioxidant to the ability of scavenging ROS and also has anti‐inflammatory and immune suppressive activities by inhibiting inflammatory cell proliferation, inducing reactive inflammatory cell apoptosis, reducing pro‐inflammatory cytokines, and down‐regulating the expression of MHC‐II . The antioxidant capacity of bilirubin is stronger than other antioxidants, such as ascorbic acid, catalase, and vitamin E. Lower serum concentration of bilirubin has been demonstrated in various chronic inflammatory diseases, including systemic lupus erythematosus, polymyositis, hypertension, and coronary artery calcification . However, to our knowledge, the role of serum bilirubin with RA has not been sufficiently investigated.…”
Section: Introductionmentioning
confidence: 96%
“…artery calcification. [11][12][13] However, to our knowledge, the role of serum bilirubin with RA has not been sufficiently investigated.…”
mentioning
confidence: 99%
“…In addition to these established risk factors, serum bilirubin is considered to be a new biomarker for various chronic diseases [1]. Research over the last two decades has shown that low levels of serum bilirubin are associated with increased risk of cardiovascular disease [2], metabolic syndrome [3], type 2 diabetes [4], stroke severity [5], certain cancers [6], autoimmune disease [7], and psychiatric disorders [8]. Bilirubin may modulate risk of these diseases by, for example, reducing lipid peroxidation and mitigating inflammation [9,10].…”
Section: Introductionmentioning
confidence: 99%